(untitled) (Eurasian Journal of Ecology, 2019)
In the modern world, anthropogenic impact on the environment is common and leads to enormous consequences, characterized in the form of land degradation, change and deterioration of soil cover, water pollution, etc. at the moment, more than 1/2 of the landscapes of the earth’s surface are subject to changes due to human impact, and, of course, this is the soil cover. About twenty per cent of the land has changed dramatically, this percentage can be attributed to built-up areas, roads, airports, including, drained, irrigated or flooded areas. Thirty percent is developed by agriculture, of which ten percent are arable lands, twenty percent are pastures. That is, human impact on the soil occurs in a variety of forms, bearing respectively direct or indirect impact. In this regard, timely actions in monitoring and assessing the current state of the soil cover are important. Therefore, the theme and purpose of this article is the disclosure of the current state of the soil cover of the Burlin district of West Kazakhstan region. To study the current state of the soil cover of the Burlin district of West Kazakhstan region, data on soil samples of 5 key sites from the territory of the Burlin district of West Kazakhstan region were taken. The data of soil cover samples of 5 key sites were made by specialists of the West Kazakhstan region in the testing laboratory. The article shows the current state of the soil cover of the Burlin district of West Kazakhstan region with the study of the main characteristics of the soil cover and with the assessment of contamination of the soil cover of the Burlin district of West Kazakhstan region. During the study of the soil cover, the excess of the maximum permissible concentration of such chemical elements as zinc, copper and Nickel was established. Key words: anthropogenic impact, pollutants, soil, soil cover, maximum permissible concentration, current state, chemical compounds.